Bibliometric analysis of global research trends in adeno-associated virus vector for gene therapy (1991-2022) - Jiang, Fengqi; Zhang, Chuanhe; Liu, Weina; Liu, Fangyuan; Huang, Haiyan; Tan, Yao; Qin, Bo (Frontiers in Cellular and Infection Microbiology, 2023)
Background Gene therapy involves introducing and editing foreign genes in the body to treat and prevent genetic diseases. Adeno-associated virus (AAV) vector has become a widely used tool in gene therapy due to its high safety and transfection efficiency. Methods This study employs bibliometric analysis to explore the foundation and current state of AAV vector application in gene therapy research. A total of 6,069 publications from 1991 to 2022 were analyzed, retrieved from the Science Citation Index Expanded (SCI-E) within the Web of Science Core Collection (WoSCC) of Clarivate Analytics. Institutions, authors, journals, references, and keywords were analyzed and visualized by using VOSviewer and CiteSpace. The R language and Microsoft Excel 365 were used for statistical analyses. Results The global literature on AAV vector and gene therapy exhibited consistent growth, with the United States leading in productivity, contributing 3,868 papers and obtaining the highest H-index. Noteworthy authors like Wilson JM, Samulski RJ, Hauswirth WW, and Mingozzi F were among the top 10 most productive and co-cited authors. The journal “Human Gene Therapy” published the most papers (n = 485) on AAV vector and gene therapy. Current research focuses on “gene editing,” “gene structure,” “CRISPR,” and “AAV gene therapy for specific hereditary diseases.” Conclusion The application of AAV vector in gene therapy has shown continuous growth, fostering international cooperation among countries and institutions. The intersection of gene editing, gene structure, CRISPR, and AAV gene therapy for specific hereditary diseases and AAV vector represents a prominent and prioritized focus in contemporary gene therapy research. This study provides valuable insights into the trends and characteristics of AAV gene therapy research, facilitating further advancements in the field.